A Systematic Literature Review of User Acceptance Factors in E-Government Services - Sari, Annisa Wulan (International Journal of Research and Applied Technology (INJURATECH), 2024)
The rapid digital transformation in the public sector has led to the widespread implementation of e-government services. However, the success of these systems heavily depends on citizen adoption and persistent usage. This study aims to explore and analyze the critical factors influencing user acceptance of e-government services through a qualitative approach. The thematic analysis reveals that user experiences closely align with the core constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Acceptance Model (TAM). Key determinants driving adoption include performance expectancy, social influence, and a strong foundational trust in government, which emerged as a pivotal factor for users in developing regions. Furthermore, the qualitative findings highlight significant real-world challenges regarding the accessibility of e-government platforms for elderly and disabled users. These insights provide a strategic roadmap for policymakers and developers to enhance inclusive and user-centric digital public services.